A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil - Zawadzki, Cláudio Henrique (2013)
Hypostomus delimai is described from the rio Tocantins, Tocantins State, and from the rio Araguaia, Pará, and Tocantins States, Brazil. The new species is distinguished from all other Hypostomus species, except from H. carinatus, H. hoplonites, and H. watwata, by the presence of five to eight (mode seven) predorsal plates limiting posterior border of the supraoccipital bone (vs. one to three plates). It can be distinguished from H. carinatus, H. hoplonites, and H. watwata by having pale spots over darker background on body and fins (vs. dark spots over lighter background). The species was only found in the middle stretches of the rio Tocantins-Araguaia basin. The first collection of specimens assigned to the new species was done in the rio Tocantins before the construction of the Tucuruí dam. Recently additional material was collected in the rio Araguaia, in a habitat that soon will be flooded for the construction of the Santa Isabel hydroelectric power station. © 2013 Sociedade Brasileira de Ictiologia.